PENDAMPINGAN PETERNAK BABI DALAM PERENCANAAN PENYEDIAAN PAKAN DI DUSUN WAIYARI DESA SULI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Fredriksz, Shirley; Joris, Lily (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2024)
Pig farming is one of the livestock sectors with good roles and prospects to be developed in Indonesia, especially in non-Muslim settlement areas. Suli Village is one of the villages on Ambon Island that can be used for pig farming development, as currently, there are already 1112 pigs being raised. The problem lies in the maintenance system, including the feeding system, which has not been implemented properly. To overcome this, assistance, counselling, and practice in formulating and providing rations for pig farmers are conducted. The method used in this activity is participatory counselling, which involves farmers in decision-making and discussion. In this activity, other feed ingredients that are not commonly used are introduced. The feeding does not consider the needs of the animals because only a 5 kg paint can is provided to the pigs in one block of the pen without considering the quantity and needs of the animals. Therefore, feeding according to qualitative and quantitative needs is introduced. The evaluation results of the activities show that the farmers have sufficiently understood the material conveyed because they have provided feed to the pigs being raised according to the quantity and needs, utilizing more agricultural and food industry waste in animal feed.